Infrastruktur Jalan, Belanja Modal dan Kesempatan Kerja: Bukti Data Panel Kabupaten Kota di Aceh - Muliadi Muliadi; Khairul Amri (Universitas Batanghari, 2019)
The main purpose of our research study is to investigate the effect of road infrastructure and capital spending on employment creation. Using a panel dataset of 23 districts/city in Aceh province from 2011 to 2018 fixed-effect methods of a panel regression model is utilized to analyze the data set. The study found that road infrastructure and capital spending have a positive and significant effect on employment creation. This thing indicates that the existence of the road infrastructure and capital spending have become the main determinant of employment creation in Aceh. Therefore, local government in Aceh has to increase the road infrastructure to improve the economic activity of the community and allocating local government budget for capital spending effectively.